How Firms Cope with Crime and Violence: Experiences from Around the World - Goldberg, Michael (World Bank, 2015)
Crime and violence inflict high costs on the private sector-costs that are rising globally, according to the World Bank's Enterprise Surveys, discussions with chambers and associations, and the Bank's Country Partnership Strategies, which reference the losses in terms of gross domestic product (GDP). In Latin America and the Caribbean, for example, losses due to crime and violence have been estimated at 9 percent of GDP in Honduras, 7.7 percent in El Salvador, and 3.6 percent in Costa Rica. In sectors such as clothing assembly, international purchasers can shift know-how and capital quickly to less violent destinations, while other sectors such as extractive industries are more likely to stay despite rising violence. Behind the statistics are human costs: lost jobs; shifting of businesses' working capital from productive uses to security firms; and an increase in contraband, fraud and corruption, and 'rule of law' issues.